Synthesis of well-crystalline lattice carbon nanotubes via neutralized cooling method - Yousefi, A.T.; Bagheri, Samira; Kadri, Nahrizul Adib; Elfghi, F.M.; Mahmood, Mohamad Rusop; Ikeda, Shoichiro (Taylor & Francis, 2015)
In this contribution, vertically aligned carbon nanotubes were synthesized by chemical vapor deposition (CVD). The effects of intrinsic disorders constructed by mobile surface contaminants on the structural perfection of carbon nanotubes (CNTs) were investigated. The results indicated a complete picture on the effect of the involved parameters on the lattice defects of modulated CNTs based on the cooling step. Raman scattering showed that the different cooling methods of the CVD preforms altered the bound complex defects of the structure of the CNTs. Moreover, an array of CNTs was removed from the silicon substrate by applying the neutralized cooling method on the CVD, while the vertical and parallel orientations were retained. The FESEM images, coupled with Raman spectroscopy results, confirm the morphological improvements of the growth CNTs based on the neutralized cooling method.